Development of the An-Nasr Mobile Application to Enhance Independent Learning Skills in Arabic Language Instruction - Khasan Aedi; Muhamad Nasrussalim; Erfan Gazali; Muhamad Towil Akhirudin (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2025)
This study addresses a gap in curriculum-aligned interactive mobile media for high school Arabic learning. Although smartphones are common, Arabic instruction remains dominated by lectures and workbooks, limiting multimodal practice and formative feedback. This research develops and validates the An-Nasr mobile learning application through the first three ADDIE stages: analysis, design, and development. Interviews with 15 Class X students and one Arabic teacher revealed that 53.3% (n=8) identified qawāʿid (grammar) as the primary learning obstacle, followed by meaning comprehension (26.7%, n=4) and vocabulary (20%, n=3), reaffirming grammar complexity as a structural barrier for non-Semitic language learners. A technology-adoption paradox emerged: 53.3% had used Duolingo and 33.3% used translation apps, yet 46.7% (n=7) never used smartphones for Arabic study, while 40% ranked mobile learning as their preferred format. This reflects systemic inhibition caused by a lack of curriculum-aligned apps and limited teacher confidence in integrating smartphone-mediated learning. The prototype was developed using PowerPoint, iSpring Suite, and Web 2 APK Builder, embedding structured modules, transliteration, native-speaker audio, annotated visuals, animations, gamified quizzes, real-time feedback, adaptive learning paths, and autosave progress tracking. Expert validation indicated high feasibility (subject-matter: 92%; media: 91%). Field trials showed strong teacher acceptance (91%) and acceptable student feasibility (77%), yielding an overall feasibility score of 87.75%, confirming prototype readiness for broader implementation. The findings reinforce that curriculum alignment, multimodal scaffolding, and meaningful formative interactivity, rather than device availability alone, determine adoption, autonomy, and learner comprehensibility in secondary Arabic digital learning environments.